Uso de data analytics para avaliar a influência econômica e social em acidentes graves de trânsito nas rodovias federais e fatores de redução de ocorrências no norte fluminense - Guerra, Cesar Iuri Rangel (Universidade do Vale do Rio dos Sinos, 2019)
Traffic accidents kill about forty-five thousand people every year in Brazil. It is of the utmost importance that those who work with road management can identify what may influence these accidents, and how they can find those factors. This essay addresses serious reports registered by the Brazilian Federal Highway Police and tries to figure out the relations between the factors that may cause them using linear regression statistical technique. At first, it will be seen that economic factors impact the number of accidents and are closely related to its reduction in Brazilian federal highways but this aspect is not the only one. We found other factors such as traffic reordering and road engineering which are also significant regarding accident decreasing. Throughout this essay, will be drawn a comparison between empirical knowledge and factual results. Sometimes one had confirmed the other but it did not always happen. For instance, using road beacons or placing speed cameras in certain areas had proved to be ineffective.
Keywords: Regressão linear; Acidentes rodoviários; Trânsito; Linear regression; Road accidents; Road traffic